Development Control And Local Authority Administration: Information System For Decision Making - Nong, Muhammad (1990)
Development control and local authority administration is an important aspect of the management of local authorities in Malaysia. It is in fact an essential duty of the local authority managers to ensure that the development control and administrative functions of the local authorities can be carried out effectively